2011
DOI: 10.1016/j.indmarman.2010.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of guanxi: Introducing the GRX scale

Abstract: This study posits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
250
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(285 citation statements)
references
References 58 publications
(91 reference statements)
1
250
0
5
Order By: Relevance
“…The last finding relates to the importance of face, favor and obligation of guanxi building in previous studies (see for example, Park & Luo, 2001;Wong & Leung, 2001). Previous studies have found that favor exchange is a challenge and failure to return favor or giving face to the other party in a relationship will be harmful for the quality of guanxi between the parties (Khan, Zolkiewski, & Murphy, 2016;Lee, Pae, & Wong, 2001;Yen, Barnes, & Wang, 2011). The findings of this study are consistent with the literature, and suggest that face, favor and guanxi are all interrelated.…”
Section: Discussion and Propositionssupporting
confidence: 88%
“…The last finding relates to the importance of face, favor and obligation of guanxi building in previous studies (see for example, Park & Luo, 2001;Wong & Leung, 2001). Previous studies have found that favor exchange is a challenge and failure to return favor or giving face to the other party in a relationship will be harmful for the quality of guanxi between the parties (Khan, Zolkiewski, & Murphy, 2016;Lee, Pae, & Wong, 2001;Yen, Barnes, & Wang, 2011). The findings of this study are consistent with the literature, and suggest that face, favor and guanxi are all interrelated.…”
Section: Discussion and Propositionssupporting
confidence: 88%
“…Ambler, 1995;Jacobs, 1979;Kipnis, 1997), the development of its measurement (e.g. Lee & Dawes, 2005;Yen, Barnes, & Wang, 2011), and the more recent debate regarding guanxi's influence on business performance in China (Geng, Mansouri, Aktas, & Yen, 2017;Luo et al, 2012;.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the cultivation of guanxi in the East encompasses relationship maintenance with family, friends and associates by means of social interactions, e.g., doing favors, sharing information, having meals and exchanging gifts (Yen et al, 2011). This concept can be a doubleedged sword.…”
Section: Guanxi Definedmentioning
confidence: 99%
“…Extant literature has identified an array of critical components of guanxi in the workplace: ganqing (affect), renqing (reciprocal exchange of favors) and xinren (trust) (Bedford, 2011;Yen et al, 2011;Zhai et al, 2013). Affect is the most frequently investigated element in guanxi studies, reflecting the tenor of a social relationship.…”
Section: Guanxi In the Workplacementioning
confidence: 99%
See 1 more Smart Citation